Implementation of Effective Financial Management Principles in Food Sector MSMEs in Baginda Village to Increase Competitiveness - FARMAN, FANJI (PT. Berkah Digital Teknologi, 2025)
This study aims to identify simple yet effective financial management practices for food-based MSMEs in Baginda Village, South Usmedang District, Sumedang Regency, using Microsoft Excel. MSMEs in this village often face challenges in managing their business finances, particularly in recording transactions, managing cash flow, and planning a structured budget. This study used a qualitative approach with data collection techniques including in-depth interviews, participant observation, and financial management training using Microsoft Excel. The results showed that before participating in the training, most MSME owners in Baginda Village had not separated their personal and business finances, making it difficult to monitor their business's financial performance. After participating in the training, which taught them how to use Microsoft Excel to create cash books, record income and expenses, and prepare monthly and annual budgets, MSME owners reported improved ability to record transactions and monitor cash flow in a more organized manner. 90% of training participants felt more confident in managing their business finances. However, challenges persist, such as limited basic accounting knowledge and a lack of skills in using advanced Excel features. Thirty percent of participants expressed difficulty using Microsoft Excel for more complex financial analysis. Therefore, it is recommended to provide further training on financial statement analysis and improve technological infrastructure in villages. This research makes a significant contribution to developing the financial capacity of MSMEs in rural areas, particularly in increasing competitiveness through more efficient and transparent financial management.